Notions of Publicist Works of G. Petkevičaitė-Bitė - Jasaitis, Juozas (Literatūra, 1967)
Publicist works were an important part in the literary activity of G. Petkevičaitė-Bitė, a Lithuanian writer of the late 19th–early 20th century. These works of G. Petkevičaitė rend possible to directly make the acquaintance of the individual of the writer with wide interests, to delineate the character of the development of the Lithuanian periodical works, that strictly joined the activity of publicist of Bitė. In this article is given a review of the fundamental problems of the publicist works of G. Petkevičaitė, the way of their solution. Bitė is presented as a democratic publicist, who analyzes in her articles the important questions of the social and cultural life of the Lithuanian people at the beginning of the 20th century. It is accentuated the progressive importance of the publicist works of Bitė in the period of the reactionary activity of Stolypin.